(3fXe GdeYdheGJ GdGSJQGJjLjI (B:s (3eONd GSJQGJjLj (B/s - (3GdRYHj, MSf Ydjs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2005)
(3fXGe GdeYdheGJ GdGSJQGJjLj h JNWjW h JWhjQ fXe GdeYdheGJ GdGSJQGJjLjI, YhGed GdfLGM GdMQLI h GdGWGQ GdYGe ddJMdjd GdGSJQGJjLj, GdeRGjG GdJfGaSjI, fXe GdeYdheGJ GdGSJQGJjLjI h GdeRGjGJ h GdJfGaSjIs
(3HHdjhZQGajG(B: (3U(B.197s
Keywords: (3GdESJQGJjLjI GdJfGaSjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s